ANALISIS LITERASI SAINS DALAM UPAYA IMPLEMENTASI PENDIDIKAN ABAD 21: Array - Nuril Laila Pradini; Bagus Rahmad Wijaya; Ana Naimatul Jannah (Citra Dharma Cindekia, 2022)
Sience literacy is an understanding of science and its application in solving problems. In scientific literacy there needs to be assistance from the teacher in its application so that learning can run with five different ways. Scientific literacy is also found in science or science. Natural science discusses everything about nature, be it abiotic or biotic. People who practice IPA are calles scientists. So literasi of science is everything or ability in application related to science that is implemented or applicated in everyday life. In already required to be. With everydays in the 21st century teaching, students are required to be independent. Because in education in the 21st era, learning is mode focused on students. Education in the era of the 21st centur is the gateway to the advancement of education in Indonesia because technological developments are developing rapidly and rapidly so that it can afeecteverydays life and is no expection in terms of learning.